'Sowing the Seeds of Love'? Determinants of Local Coalition Formation and Termination between the CDU and the Greens, 1994–2016. Issue 3 (3rd July 2018) - Gross, Martin
Abstract : Drawing on empirical evidence from 11 CDU–Green coalitions in large German municipalities, this article investigates the determinants of formation and termination of black–green minimal winning coalitions. Such coalitions are likely to be formed if the mayor is a party member of either the CDU or the Greens, if one of the two parties dominates the local party system, and if the SPD suffers from severe vote losses. Furthermore, the results indicate that CDU–Green coalitions are primarily formed if neither the CDU nor the Greens have gained a parliamentary majority with their 'usual' coalition partners. Ideological connectivity, however, does not play a major role. Regarding coalition stability, Christian Democrats and Greens are able to govern successfully for an entire legislative term in most of the cases. If a coalition is terminated early, however, this is due to a party breaking the coalition agreement by voting on specific policies together with the SPD in the local council.